A review: Effect of Input Parameters on Electrical Discharge Machining - Singh, Hira (International Journal For Research In Mechanical & Civil Engineering, 2015)
Electrical discharge machining is a non conventional machining process. EDM is very useful for the machining of very hard material. There is no direct contact between the workpiece and tool electrode. This paper shows the effects of input parameters on the response parameters. In other words this shows the effect of the current, voltage, duty factor, etc. on the material removal rate, surface roughness etc.